Dose of trinexapac-ethyl and the age of seedling influence the stimulatory effect in Eucalyptus - da Silveira, M. R.F. [UNESP]; Bacha, A. L. [UNESP]; Braga, A. F. [UNESP]; Carrega, W. C. [UNESP]; da Costa Aguiar Alves, P. L. [UNESP] (Forest Research Institute Malaysia, 2021)
Trinexapac-ethyl (TE) has recently been shown to have a stimulatory effect on the initial growth of Eucalyptus seedlings. However, the optimal dose and seedling age at which TE should be applied has not been assessed. The objective of our study was to evaluate the effects of sub-doses of TE on the initial growth of eight Eucalyptus clones. The experiment was conducted in an open area. The treatments were arranged in an 8 × 3 factorial scheme, meaning eight Eucalyptus clones and three doses of TE (0, 15 and 30 g a.i. ha-1) sprayed at 70 days after planting. Plant height, stem diameter, shoot and root dry mass, and leaf area were evaluated. Eucalyptus clones differed in their growth regardless TE application. TE did not negatively affect the growth of any clones but doses used in our study were not sufficient to give a significant positive effect on growth when applied at 70 days after planting. We suggest that older Eucalyptus seedlings need higher doses of TE to reveal potential stimulatory effects on growth of the plants.
Keywords: Chemical ripener; Eucalyptus clones; Gibberellins; Plant growth regulator